Pengetahuan dan Sikap berhubungan dengan Perilaku Penurunan Tekanan Darah pada Lanjut Usia dengan Hipertensi - Hasanah, Nurul; Fatmawati, Tina Yuli; Armina, Armina; Zein, Zafrullah (Prosiding Seminar Kesehatan Nasional, 2023)
Hypertension is a condition where there is an increase in systolic blood pressure 140 mm Hg or diastolic blood pressure 90 mm Hg. Hypertension is often referred to as the "silent killer". Hypertension is still high located at the Simpang IV Sipin Health Center Jambi City with a total of 1,865 which can be caused by various factors from knowledge, attitudes to behavior. The purpose of this study was to determine whether there was a relationship between knowledge and attitudes with blood pressure reduction behavior in elderly patients with hypertension at the Simpang IV Sipin Health Center Jambi City. The population in this study were all elderly with hypertension at the Simpang IV Sipin Health Center. Based on the research, it was found that there was a positive relationship between knowledge and behavior with a correlation coefficient of 0.47 and there was a positive relationship between attitudes and behavior with a correlation coefficient of 0.41 greater r table 0.36. It was concluded that there was a relationship between knowledge and attitude and behavior in reducing blood pressure in the elderly with hypertension at the Simpang IV Sipin Health Center, Jambi City.Â